2006
DOI: 10.1093/humrep/del326
|View full text |Cite
|
Sign up to set email alerts
|

Sperm DNA integrity assessment in prediction of assisted reproduction technology outcome

Abstract: DFI can be used as an independent predictor of fertility in couples undergoing IUI. As a result, we propose that all infertile men should be tested with SCSA as a supplement to the standard semen analysis. When DFI exceeds 30%, ICSI should be the method of choice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

29
544
5
13

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 652 publications
(591 citation statements)
references
References 40 publications
29
544
5
13
Order By: Relevance
“…Similar cut-offs of 28 % for 33 IUI/IVF/ICSI/ cycles [36], 20 % in a group of 104 IVF and ICSI cycles [4] and 27 % for 113 IVF and ICSI cycles have been reported [27]. [10] have also shown the importance of this chromatin assay as an independent predictor in assisted reproduction outcome. The study proved that the outcome parameters like biochemical pregnancy, clinical pregnancy and delivery were significantly decreased in couples with DFI >30 % as compared with couples with DFI ≤30 %.…”
Section: Discussionsupporting
confidence: 58%
“…Similar cut-offs of 28 % for 33 IUI/IVF/ICSI/ cycles [36], 20 % in a group of 104 IVF and ICSI cycles [4] and 27 % for 113 IVF and ICSI cycles have been reported [27]. [10] have also shown the importance of this chromatin assay as an independent predictor in assisted reproduction outcome. The study proved that the outcome parameters like biochemical pregnancy, clinical pregnancy and delivery were significantly decreased in couples with DFI >30 % as compared with couples with DFI ≤30 %.…”
Section: Discussionsupporting
confidence: 58%
“…Several studies have been carried out in order to identify whether DNA damage may be considered a good predictor of ART outcomes and how it may influence pregnancy rates. In one of the largest ever reported studies investigating the predictive value of a DNA fragmentation assay in the determination of intrauterine insemination (IUI), IVF, and ICSI, the DFI was identified as a new determining factor in ART outcome [22].…”
Section: Discussionmentioning
confidence: 99%
“…Semen analysis provides limited prognostic information on fertility, and recent studies indicated that the integrity of sperm DNA might be a more accurate and precise predictor of fertility [3] an intact DNA is necessary for the correct transmission of genetic materiel to the next generation. High levels of sperm DNA damage have been reported to affect fertility potential, increase the risk of recurrent miscarriages, decrease the chances of a successful implantation, and possibly lead to negative effects on the health of offspring [4,5]. Sperm DNA integrity as assessed by terminal desoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) [6], sperm chromatin structure assay (SCSA) [7,8], and Comet assay [9], were also shown to be compromised with advancing age.…”
Section: Introductionmentioning
confidence: 99%